Do China and Russia Undermine US Sanctions? Evidence from DiD and Event Study Estimation - Jerg Gutmann; Matthias Neuenkirch; Florian Neumeier (University of Hamburg, Institute of Law and Economics (ILE), 2022)
A frequently employed argument against imposing international sanctions is that rival superpowers are likely to bust sanctions to simultaneously shield the target, harm the sender, and make a profit. We evaluate the legitimacy of this concern by studying the effect of US sanctions on trade flows between sanctioned and third countries during the period 1995-2019 using panel difference-in-differences estimations and an event study design. Motivated by the claim that China and Russia purposefully undermine US sanction efforts, we test whether target countries' trade with China and Russia increases under US trade sanctions. We find no evidence for systematic sanction busting. Russia does not change its trade patterns with sanctioned countries. Trade of targets of US sanctions with China declines even more than trade with the US. These general patterns are reconfirmed for trade in different groups of commodities. In addition, we find some evidence that a reduction in industrial value added and a devaluation of the domestic currency of the target country are transmission channels through which US sanctions hamper trade with third countries.
Keywords: F13; F14; F50; F51; F52; F53; K33; 330; Geopolitics; international political economy; international sanctions; trade substitution